A method to define SoS requirements. (1st January 2014) - Walker, Randy G.; Keating, Charles B.; Gheorghe, Adrian V.; Unal, Resit; Pyne, James
The purpose of this paper, following completion of the initial research effort, is to provide an update to the previously-published article in this same journal, which examined the nature of the issues surrounding SoS requirements definition and discussed and demonstrated an emerging methodology. With the related research stage complete, the now SoS requirements definition method shows promise for being transportable to a wide range of SoS domains and can significantly enhance requirements practices for engineering SoS to provide element system managers and engineers a higher level SoS focus to their efforts while still maximising their autonomy to achieve system-level requirements. The method combines top-down, bottoms-up approaches to discerning and deriving unifying SoS requirements. The end result is a set of SoS requirements that are more granular than high-level capability objectives yet more abstract than the detailed system requirements.